Dataset for the new insights into methane hydrate inhibition with blends of vinyl lactam polymer and methanol, monoethylene glycol, or diethylene glycol as hybrid inhibitors - Anton P. Semenov; Yinghua Gong; Vladimir I. Medvedev; Andrey S. Stoporev; Vladimir A. Istomin; Vladimir A. Vinokurov; Tianduo Li (Data in Brief, 2023)
Three-phase equilibrium conditions of vapor–aqueous solution–gas hydrate coexistence for the systems of CH4–H2O–organic thermodynamic inhibitor (THI) were experimentally determined. Hydrate equilibrium measurements for systems with methanol (MeOH), monoethylene glycol (MEG), and diethylene glycol (DEG) were conducted. Five concentrations of each inhibitor (maximum content 50 mass%) were studied in the pressure range of 4.9–8.4 MPa. The equilibrium temperature and pressure in the point of complete dissociation of methane hydrate during constant-rate heating combined with vigorous mixing of fluids (600 rpm) in a high-pressure vessel were determined. We compared our experimental points with reliable literature data. The coefficients of empirical equations are derived, which accurately describe hydrate equilibrium conditions for the studied systems. The effect of THI concentration and pressure on methane hydrate equilibrium temperature suppression was analyzed.In the second stage, we studied the kinetics of methane hydrate nucleation/growth in systems containing a polymeric KHI (0.5 mass% of N-vinylpyrrolidone and N-vinylcaprolactam copolymer) in water or THI aqueous solution. For this, temperatures, pressures, and subcoolings of methane hydrate onset were measured by rocking cell tests (RCS6 rig, ramp cooling at 1 K/h). Gas uptake curves characterizing the methane hydrate crystallization kinetics in the polythermal regime were obtained.